REORIENTASI DAN STRATEGI PENGUSAHA DALAM MENCAPAI PENINGKATAN KINERJA USAHA MIKRO DAN KECIL (UMK) DI WATAMPONE - Astuti, Yuli; Abdulahanaa, Abdulahanaa; Sahaka, Arifin (Jurnal Ilmiah Al-Tsarwah, 2023)
This research discusses the reorientation and strategies of entrepreneurs in achieving improved performance of Micro and Small Enterprises (MSEs) in Watampone from a sharia management perspective.The main issue is the reorientation and strategies of entrepreneurs in achieving improved performance of Micro and Small Enterprises (MSEs) in Watampone.The objective of this research is to answer problems related to the entrepreneurial orientation model in improving the performance of MSEs in Watampone, the entrepreneurial strategies in improving the performance of MSEs in Watampone, and the orientation and strategies of entrepreneurs in improving the performance of MSEs in Watampone from a sharia management perspective. This research is a field research using psychological and sharia economic approaches. The types of data used are primary and secondary data. This research uses observation, interviews, and documentation methods. The data processing is done by conducting data collection, data reduction, data display, and conclusion drawing. The results showed that: first, it is empirically found that the orientation model used by entrepreneurs in Watampone is the skills of creating renewal, taking advantage of opportunities, being consistent, meticulous in improving their business performance. Second, empirically the strategies used by entrepreneurs in Watampone in improving their business performance are being creative, always utilizing available resources, building relationships, and managing capital properly.Third, the implementation of entrepreneurial orientation and strategies in Watampone has been carried out well and is in line with sharia management.